Salp swarm algorithm-based optimal load frequency control of hybrid renewable power systems with communication delay and excitation cross-coupling effect - Hasanien, Hany M.; El-Fergany, Attia A. (Electric power systems research, 2019)
•Salp swarm algorithm (SSA) is applied for fine-tuning of PID parameters.•System nonlinearity and wind farms uncertainty are considered.•The effect of cross-coupling between the excitation and LFC loop is investigated.•Real wind speed data and real sun irradiations are utilised for realistic studies.•The dynamic responses are investigated and analyzed plus comparisons. This paper proposes a new application of the salp swarm algorithm (SSA) to fine-tune the gains of proportional-integral-derivative (PID) controllers of load frequency control (LFC) of a multi-area hybrid renewable nonlinear power system. To analyze the system nonlinearity, a dead-band is implemented in the governor model, a generation rate constraint is employed with the turbine model, and a communication delay time of phase measuring unit devices is carried out in the secondary automatic LFC loop. An exact model is established to take into consideration the effect of cross-coupling between the excitation control system and LFC loop. A single and multi-objective functions are performed to test the validity of the proposed controllers. To obtain a more realistic study, real wind speed data are involved in the wind farm model and real sun irradiations for a photovoltaic system that captured from a field test are incorporated to check the validity of the SSA-PID controllers under power system nonlinearities and renewable energy sources variability and uncertainties. The effectiveness of SSA-PID controller is compared with other optimization methods based-PID controller under several operating conditions. With the proposed controller, the LFC dynamic responses of multi-area hybrid nonlinear power systems shall be further enhanced.